2022
DOI: 10.1002/14651858.cd014936.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Smoking cessation for secondary prevention of cardiovascular disease

Abstract: BackgroundSmoking is a leading cause of cardiovascular disease (CVD), particularly coronary heart disease (CHD). However, quitting smoking may prevent secondary CVD events in people already diagnosed with CHD. ObjectivesTo examine the impact of smoking cessation on death from CVD and major adverse cardiovascular events (MACE), in people with incident CHD. Search methodsWe searched the Cochrane Tobacco Addiction Group's Specialised Register, CENTRAL, MEDLINE, Embase, Cumulative Index to Nursing and Allied Healt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 116 publications
0
7
0
2
Order By: Relevance
“…In a meta-analysis of 18 studies and 17 982 adult participants with CHD who were smoking at the time of diagnosis, smoking cessation was associated with a lower risk of cardiovascular death (HR, 0.61 [95% CI, 0.49–0.75]). 71 A secondary analysis including 9 studies and 11 352 participants showed that smoking cessation was associated with a lower risk of nonfatal stroke (HR, 0.70 [95% CI, 0.53–0.90]).…”
Section: Stroke (Cerebrovascular Diseases)mentioning
confidence: 99%
“…In a meta-analysis of 18 studies and 17 982 adult participants with CHD who were smoking at the time of diagnosis, smoking cessation was associated with a lower risk of cardiovascular death (HR, 0.61 [95% CI, 0.49–0.75]). 71 A secondary analysis including 9 studies and 11 352 participants showed that smoking cessation was associated with a lower risk of nonfatal stroke (HR, 0.70 [95% CI, 0.53–0.90]).…”
Section: Stroke (Cerebrovascular Diseases)mentioning
confidence: 99%
“…Additionally, smoking is known to increase total serum cholesterol, VLDL, LDL, and triglyceride serum concentrations, which in turn increases the risk of atherosclerosis and other forms of CVDs [50]. The cessation of smoking was found to significantly reduce the risk of CVD events such as nonfatal myocardial infarctions, nonfatal strokes, and death [51]. The repercussions of smoking also do not just end at the individual level.…”
Section: Smokingmentioning
confidence: 99%
“…Bei Patienten mit Lungen-, kardiovaskulären-und Krebserkrankungen sowie einer Vielzahl weiterer chronischer Erkrankungen führt der Rauchstopp zu einer Verbesserung der Symptomatik und Prognose [5]. Dies konnte beispielhaft das Cochrane-Review zur Tabakentwöhnung und koronaren Herzerkrankung zeigen, wo der Rauchstopp das Risiko für die KHK um ein Drittel senkt [29].…”
Section: Grundlagen Der Tabakentwöhnungunclassified